The Quantum Symphony of Life: Insights into Biological Systems - Igor Orzhelskyi; Andrey Kuznetsov; Elena Van Dijk (Advanced Research in Biological Science Vol. 9, 2024)
The study effectively introduces and explores complex concepts in condensed matter physics, quantum mechanics and their applications in various systems, including biological ones. The connection between quantum principles and real-world technologies, such as quantum cryptography and computers, adds practical relevance. Integrating ERI technology in the context of quantum mechanisms provides a bridge between theoretical concepts and potential practical applications in healthcare. The functioning of a biological systems, maintaining the dynamic stability of its homeostasis, is provided by regulatory systems. Traditionally, such systems include the nervous and humoral systems of regulation. The third regulatory system of the body, which provides communication in the body, distance interactions according to the “informational” principle, is not considered. For this reason, the understanding of the law of nature – “substance-energy-information”, uniting the foundations of any matter, is very limited in biology. The significant synchronization of oscillations of their structures and processes allows these systems to effectively respond to weak regulatory signals and to form their own response signals of sufficient intensity in the system of communication links and interactions. This article provides a summary of the basic rules and principles of the interaction of Matter, Energy and Information from a quantum perspective.